Avaliação do estado nutricional de vinhedos e sua correlação com a produção de uvas viníferas de qualidade - Fogaça, Aline de Oliveira (2005)
Petioles (taken at bloom time and 30 days after) from three Vitis vinifera varieties (Pinot noir, Cabernet Sauvignon and Merlot) were analysed during two consecutive years for mineral content. Samples of grape berries were taken during the ripening process. Field data (temperature, precipitation, heat summation) and Brix, total acids, and pH were also followed during the two seasons. This work was carried out with following aims: a) evaluate petiolar analysis as a useful tool to check vineyard s nutritional status and help to soil fertilizer additions decisions; b) follow the potassium mineral content during the ripening process and its influence in pH values; c) connect the potassium grape content with potassium petiolar content. Petiolar analysis was efficient for mineral content evaluation in vineyards; a more correct soil amendment showed better approach for the real need of minerals. As expected the rise in potassium content was followed by a rise in pH values and the drop was followed just by more stable pH values. The reason for this behavior is in acidity values, which dropped during the ripening process. So, the correlation among high pH values, low titratable acidity values and potassium content might be suggested. A relationship between petiolar analysis and grape potassium content is another logical deduction.